TINJAUAN PENERAPAN ASPEK ERGONOMI PADA RUANG PENYIMPANAN BERKAS REKAM MEDIS DI RUMAH SAKIT BHAYANGKARA TK. II SARTIKA ASIH BANDUNG - Suharto, Suharto; Yusup, Ahmad Maulana (Jurnal TEDC, 2024)
Based on the results of observations, preliminary studies and interviews, researchers found that there was discomfort when in the Medical Records Storage Room. The discomfort in the storage room is very disturbing for the officers because the temperature in the room is not suitable. The aim to be achieved by the author is to get an overview of the review of the application of ergonomic aspects in the storage room at Bhayangkara Tk Hospital. II Sartika Asih Bandung. The method that researchers used in this research, namely qualitative methods. Qualitative research is research that emphasizes quality or the most important thing in goods or services. Researchers collected data by: observation, interviews, literature study. There are 2 separate medical record rooms. In the first room there is an assembly, distribution room, 12 roll o'packs, 4 tables, 5 chairs, 3 ACs, 10 lamps, 2 ventilation fans and 1 fire extinguisher. In the second room there is a retention room, 4 roll o'packs, and 33 storage shelves, 2 chairs, 1 table, 1 AC, 5 lamps, 3 ventilation fans, and 1 fire extinguisher. The impact that occurs is that officers get tired easily, officers become hampered in searching for files, officers' health becomes compromised due to ventilation fans not functioning. Efforts that can be made by storage officers include submitting an ergonomics software, submitting an additional room. The hospital will try to add these facilities to the storage room at Bhayangkara TK Hospital. II Sartika Asih Bandung.